Fixation of the short-term central venous catheter. A comparison of two techniques - Leal,Mário Lúcio Marques (2017)
Abstract Purpose: To compare the fixation of the central venous catheter (CVC) using two suture techniques. Methods: A clinical, analytical, interventional, longitudinal, prospective, controlled, single-blind and randomized study in adult, intensive care unit (ICU) patients. After admission and indication of CVC use, the patients were allocated to the Wing group (n = 35, catheter fixation with clamping wings and retainers) or Shoelace group (n = 35, catheter fixation using shoelace cross-tied sutures around the device). Displacement, kinking, fixation failure, hyperemia at the insertion site, purulent secretion, loss of the device, psychomotor agitation, mental confusion, and bacterial growth at the insertion site were evaluated. Results: Compared with the Wing group, the Shoelace group had a lower occurrence of catheter displacement (n=0 versus n =4; p = 0.04), kinking (n=0 versus n=8; p=0.001), and fixation failure (n=2 versus n=8; p=0.018). No significant difference was found in bacterial growth (n=20 versus n=14; p=0.267) between groups. Conclusion: The Shoelace fixation technique presented fewer adverse events than the Wing fixation technique.